STRATEGIC HUMAN RESOURCE MANAGEMENT - Hadiati, Eti; Maulidamayry, Rizki; Ayu, Oktalia Sapitri; Merhida, Merhida; Novita, Putri; Pramudya, Kartika Dwi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study discusses the implementation of strategic human resource management (SHRM) as a crucial approach to aligning organizational goals with human resource strategies. The research aims to identify the challenges organizations face in integrating SHRM into their operations and evaluate the impact of these practices on organizational performance. Using a qualitative methodology, the study examines case studies of various industries to provide a comprehensive analysis of SHRM applications. The findings reveal that effective SHRM enhances employee engagement, fosters innovation, and improves competitive advantage. Moreover, the research highlights the significance of leadership commitment, technological adoption, and continuous skill development as key drivers of successful SHRM. This paper underscores the importance of adopting a holistic and adaptive HR management framework to meet the evolving demands of the global business environment.